Prognostic factors of survival time for breast cancer patients in Pietersburg Hospital in Limpopo Province of South Africa - Hlungwani, Collen (My University, 2024)
The breast cancer metastasis in women had devastating disease throughout the world with patient goals aimed at improving quality of life and prolonged survival. Advanced treatments have been impressive for women with early-stage disease, and women diagnosed with advanced forms of breast cancer have also benefitted. To achieve this goal, more information is needed. Hence, the purpose of the study was to apply survival models and methods to identify breast cancer-related survival factors. These models were exponential, Weibull, log-normal, log-logistic, Cox proportional hazard and Kaplan-Meier method. The findings revealed that pre-menopause, human epidemic growth factor 2, positive oestrogen receptor, positive progesterone receptor, AJCC stage 4, endocrine therapy, surgery, N-stage, M1 stage, T-stage were significantly associated with better prognosis in Petersburg Oncology Hospital. It was further concluded that breast cancer patients who experienced lower survival are those breast cancer women who were diagnosed at late-stage when cancer cells had already advanced.
Thesis (M. Sc. (Statistics)) -- University of Limpopo, 2024
Keywords: Breast cancer; Disease; Advanced treatments; Models; Breast -- Cancer -- Statistics; Breast --Cancer -- Treatment; Breast -- Cancer; Statistics -- Methodology; Survival analysis (Biometry)